Escaping Hitler : A Jewish Haven in Chile - Goldschmidt Wyman, Eva (Book collections on Project MUSE., 2013)
This is the personal story of Eva Wyman and her family's escape from Nazi Germany to Chile in the sociohistorical context of 1930s and 1940s, a time when the Chilean Nazi party had an active presence in the country's major institutions. Based primarily on interviews with German Jewish refugees and family correspondence, the author provides an intimate account of Jews in Germany in the 1930s as Nazi controls tightened and family members were taken to Riga concentration camp. She recounts Kristallnacht in Stuttgart, where her father was principal of the Jewish school, his imprisonment in Dachau, and his release and immigration to Great Britain. This book details the family's escape from Germany and subsequent life in Chile, providing an intimate look at daily life on the steam ship Conte Grande during the voyage from Italy to Chile in 1939, Nazi espionage and anti-Semitic activity in Chile, and the Nazi influence in South America in general. Recounted in an intimate and personal style, this book immerses the reader in an extraordinary chapter of contemporary Jewish history - both inside Germany and South America.